Growth and Production of Organic Tomatoes (Solanum Lycopersium) on the Application of Organic Fertilizer and Mulch Types - A Syaiful, Syatrianty; Kasim, Nurlina; Afnita, Dea (Hasanuddin University, 2023)
This research aimed to analysis the effect of various types of organic fertilizer and mulch types on growth and production of tomato plants. Research was conducted at Liliriaja District, Soppeng Regency, South Sulawesi on January-June 2023. This research used a factorial 2 factor experiment in Randomized Complete Block Design (RCBD) as the environmental design. The first factor is organic fertilizer with 3 types: chicken compost 15 tons ha-1, cow manure 15 tons ha-1, and goat manure 15 tons ha-1. The second factor is mulch with 3 types: without mulch, 10 tons ha-1 rice husk mulch, and plastic mulch. The results showed that there was an interaction between chicken compost fertilizer and rice husk mulch at the number of fruit / plot (260.00 fruits), fruit weight / plot (8.00 kg) and production (26.67 tons ha-1). Chicken compost in 15 ton ha-1 gave the highest number of fruit /plant (18.93 fruits) and fruit weight/plant (727.00 g).